1998
DOI: 10.1038/sj.bmt.1701473
|View full text |Cite
|
Sign up to set email alerts
|

Autologous transplantation of mobilized peripheral blood CD34+ cells selected by immunomagnetic procedures in patients with multiple myeloma

Abstract: Summary:In the use of autologous PBPC transplantation in patients with multiple myeloma, contamination of PBPC with myeloma cells is commonly observed. Enrichment for CD34 ؉ cells has been employed as a method of reducing this contamination. In this study the reduction of myeloma cells in PBPC was accomplished by the positive selection of CD34 ؉ cells using immunomagnetic bead separation (Isolex 300 system). PBPC were mobilized from 18 patients using cyclophosphamide (4.5 g/m 2 ) and G-CSF (10 g/kg/day). A med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
3

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 30 publications
0
24
0
3
Order By: Relevance
“…A variety of approaches have been developed in an attempt to improve the outcome of high-dose therapy in multiple myeloma patients, including tandem highdose therapy, 25,26 reduced intensity allogeneic transplantation ,27,28 purging strategies based either on negative or positive selection, [29][30][31][32][33][34][35][36][37][38][39] and new approaches to conditioning. Although the present study used a combination of melphalan and TBI for conditioning, it has since been established that high dose melphalan alone is less toxic and at least as effective as regimens including total body irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of approaches have been developed in an attempt to improve the outcome of high-dose therapy in multiple myeloma patients, including tandem highdose therapy, 25,26 reduced intensity allogeneic transplantation ,27,28 purging strategies based either on negative or positive selection, [29][30][31][32][33][34][35][36][37][38][39] and new approaches to conditioning. Although the present study used a combination of melphalan and TBI for conditioning, it has since been established that high dose melphalan alone is less toxic and at least as effective as regimens including total body irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…In most previously published works, mobilization of stem cells was obtained with cyclophosphamide and G-CSF. [11][12][13][14]18 This myelosuppressive procedure potentially exposed patients to infectious complications and required hospitalization. Although the number of CD34 ϩ cells collected appears to be superior after priming with high-dose cyclophosphamide followed by G-CSF as compared to G-CSF alone, [19][20][21][22] G-CSF alone in steady-state allowed efficient stem cell mobilization especially when performed in slightly pretreated patients and with responsive disease at the time of mobilization.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, positive selection of CD34 ϩ cells reduces the contamination of myeloma cells from the apheresis products up to 2 to 4 logs and provides a progenitor cell suspension capable of restoring normal hematopoiesis. [8][9][10][11][12][13][14] In order to evaluate the clinical impact of CD34 ϩ cell selected peripheral blood stem cell autologous transplantation in MM, we performed a case controlled analysis. 21 …”
Section: Introductionmentioning
confidence: 99%
“…4,13,18 Moreover, both G-CSF and GM-CSF appear to be equivalent when added to cyclophosphamide. 19 It has also been suggested that a combination of cyclophosphamide, etoposide and G-CSF is superior to either cyclophosphamide plus growth factor or G-CSF alone in patients with multiple myeloma. 10 We combined cyclophosphamide with etoposide and G-CSF and added paclitaxel because of its ability to mobilise PBSC in other malignancies.…”
Section: Discussionmentioning
confidence: 99%